2023
DOI: 10.3390/ijerph20054316
|View full text |Cite
|
Sign up to set email alerts
|

Variable Resistance—An Efficient Method to Generate Muscle Potentiation: A Systematic Review and Meta-Analysis

Abstract: Variable resistance (VR) is a methodology that has shown good results in developing muscular strength and power. However, no updated information relates to the use of VR as an activation to trigger post-activation performance enhancement (PAPE). The primary objective of this systematic review and meta-analysis was to review and qualitatively describe studies published between 2012 and 2022 that used VR to generate PAPE in muscle power-dominant sports. The secondary objective was to calculate the effect size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Significant increases (P < .05) in CMJ height (5.3% -6.5%), maximum power (4.4% -5.9%), force development velocity (12.9% -19.1%), concentric knee angular velocity (3.1% -4.1%) and mean concentric vastus lateralis activity (27.5% -33.4%) were found at all time points following VR. The study described above was confirmed in a systematic review and meta-analysis conducted by Huerta Ojeda et al 110 which examined the effects of VR on muscle power in sports requiring explosive performance. Studies published between 2012 and 2022 were analyzed, assessing methodological quality and risk of bias.…”
Section: Accommodating Resistance Trainingmentioning
confidence: 62%
See 1 more Smart Citation
“…Significant increases (P < .05) in CMJ height (5.3% -6.5%), maximum power (4.4% -5.9%), force development velocity (12.9% -19.1%), concentric knee angular velocity (3.1% -4.1%) and mean concentric vastus lateralis activity (27.5% -33.4%) were found at all time points following VR. The study described above was confirmed in a systematic review and meta-analysis conducted by Huerta Ojeda et al 110 which examined the effects of VR on muscle power in sports requiring explosive performance. Studies published between 2012 and 2022 were analyzed, assessing methodological quality and risk of bias.…”
Section: Accommodating Resistance Trainingmentioning
confidence: 62%
“…One such precaution is that the elastic should offer resistance and, therefore, be in maximum tension at the start of the movement and that it loses the resistance it offers at the sticking point. Currently, studies can be found in the literature demonstrating the effectiveness of this methodology for the manifestation of PAP, showing that through the use of accommodating resistance, the phenomenon can be manifested with recovery times between the conditioning activity and the subsequent explosive activity [108][109][110] . Mina et al 109 compared the effects of using squats with or without elastic bands on vertical jump performance.…”
Section: Accommodating Resistance Trainingmentioning
confidence: 99%
“…Considering PAPE research, the authors show particular interest in a combination of free weight resistance and accommodating resistance 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 that was proven to be effective in generating muscle potentiation. 31 However, the researchers seem to focus in their studies solely on accommodating resistance - a training method that involves using elastic bands or chains and challenges athletes to constantly accelerate through a given range of motion. 32 Only four studies compared the accommodating resistance with other types of resistance: two with isoinertial resistance 22 , 25 and two with traditional free weight resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Current PAPE research indicates that various PAPE protocols may be implemented and acutely enhance subsequent post-CA performance. The authors introduced and found beneficial effects of various application methods such as isometric CA 12 , 13 , traditional resistance 3 , 14 , accommodating resistance 15 , 16 or flywheel devices 17 . The approach to evaluate PAPE responses may differ between the protocols—the post-CA explosive exercise may be introduced after a single set of a CA 18 , after multiple sets of the same CA 19 or between each set of the same CA 20 .…”
Section: Introductionmentioning
confidence: 99%